2002
DOI: 10.1002/jrs.860
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive method for the quantification of the average particle diameter of latex as water‐based emulsions by near‐infrared Fourier transform Raman spectroscopy

Abstract: Vibrational spectroscopy is utilized to characterize compounds, but it has never been applied to quantitative morphological analysis of polymers in a mass. By using near-infrared Fourier transform Raman spectroscopy coupled with multivariate data analysis, the average particle diameter of macroscopic size in water-based latex emulsions was successfully quantified with correlation coefficients >0.95, both in calibration (known samples, n = 36) and in prediction (unknown samples, n = 11) against conventionally m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…Given that Raman scattering depends on the number of molecules, then in a mixture with two components illuminated and viewed, the concentration proportion is the mole fraction. 46 Therefore, …”
Section: Raman Response From Mixed and Dispersed Cntsmentioning
confidence: 99%
“…Given that Raman scattering depends on the number of molecules, then in a mixture with two components illuminated and viewed, the concentration proportion is the mole fraction. 46 Therefore, …”
Section: Raman Response From Mixed and Dispersed Cntsmentioning
confidence: 99%
“…Secondly, slurry samples can be measured directly since water has a very weak Raman spectrum. This advantage of Raman spectroscopy has been successfully employed in the investigations of emulsion and suspension formulations [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Raman has been used to follow monomer concentrations,1, 54–56 and it has been shown that Raman spectra are affected by particle size in emulsion polymerization 57, 58. Many of the foregoing referenced works, and others, combine IR and Raman measurements 59, 60…”
Section: Measurement Of Monomer and Polymer Characteristics During Pomentioning
confidence: 99%